BEHAVIORAL ECONOMICS IN PUBLIC POLICY: A REVIEW OF NUDGE-BASED INTERVENTIONS AND ECONOMIC OUTCOMES - Dadi Kuswandi; Radi Sahara; Sri Wulan Windu Ratih; Wiarsih Febriani (Jurnal Ekonomi dan Manajemen, 2025)
This study provides a systematic literature review on the application of behavioral economics, particularly the nudge theory, in shaping public policy and influencing economic outcomes. As traditional economic models assume rational decision-making, behavioral approaches challenge this by highlighting systematic biases, heuristics, and cognitive limitations in individual choices. This review synthesizes findings from 50 peer-reviewed articles and policy reports from 2010 to 2024, exploring how nudge-based interventions have been utilized in domains such as taxation, savings, energy conservation, and public health. The study categorizes nudges into types—defaults, simplifications, reminders, and social norm framing—and evaluates their effectiveness across various economic settings. The findings suggest that nudges are cost-effective, scalable, and adaptable, but their long-term impact and ethical considerations remain contested. This paper contributes to the discourse on evidence-based policymaking by offering insights into the design and evaluation of behavioral tools for public governance.